Real-world efficacy and safety of combined first-line treatment with PARP inhibitors and novel hormonal therapy in mCRPC patients with HRR gene mutations - Guo, Andong; Wu, Chenrui; Cao, Jishuang; Zhu, Kejia; Ding, Sentai (Frontiers in Genetics, 2024)
ObjectiveThis study evaluated the real-world efficacy and safety of combining PARP inhibitors with novel hormonal therapy (NHT) as a first-line treatment in Chinese patients with metastatic castration-resistant prostate cancer (mCRPC) harboring homologous recombination repair (HRR) gene mutations.MethodsWe enrolled 41 mCRPC patients who received at least 1 month of combined treatment with PARP inhibitors and NHT. Patients were divided into two groups: Cohort A (mutations in BRCA1, BRCA2, or ATM genes) and Cohort B (mutations in other HRR genes). The primary endpoint was imaging-based progression-free survival (PFS), with secondary endpoints including objective response rate (ORR), disease control rate (DCR), overall survival (OS), PSA50 response, and adverse events (AEs). To ensure accurate research results and control confounding factors, we will employ multivariate Cox proportional hazards models to evaluate key variables affecting mCRPC patient survival outcomes.ResultsThis study enrolled 41 patients, 22 in Cohort A and 19 in Cohort B. The median PFS for all patients was 21.8 months, and the median OS had yet to be reached. The overall ORR was 48.8%, and the DCR was 61.0%. Specifically, the median PFS for Cohort A was 21.8 months compared to 14.5 months for Cohort B. The median OS had yet to be reached for either cohort. Regarding efficacy, 81.8% of patients in Cohort A and 73.7% in Cohort B achieved a PSA50 response. Imaging assessments showed ORRs of 54.6% for Cohort A and 42.1% for Cohort B, with DCRs of 72.7% and 47.4%, respectively. 85.4% of patients experienced grade 1 or 2 adverse events, and 51.2% encountered grade 3 or 4. In the multivariate Cox regression analysis focusing on PFS, the Gleason score was identified as a significant predictor (HR = 5.8, 95% CI: 1.65–20.2, p = 0.006).ConclusionCombined first-line treatment with PARP inhibitors and NHT is effective and well-tolerated in mCRPC patients with HRR gene mutations, particularly those with BRCA1, BRCA2, or ATM mutations. These findings underscore the potential of this therapeutic combination in managing mCRPC in the Chinese population, suggesting a favorable outcome for those with specific genetic backgrounds.